The Role of the Bone Marrow Microenvironment in the Response to Infection - Johnson, Courtney B.; Zhang, Jizhou; Lucas, Daniel (Frontiers in Immunology, 2020)
Hematopoiesis in the bone marrow is the main source of immune cells. Hematopoiesis is regulated by a diverse cellular microenvironment that supports stepwise differentiation of multipotent stem cells and progenitors into mature blood cells. Blood cell production is not static, and the bone marrow has evolved to sense and respond to infection by rapidly generating immune cells that are quickly released into the circulation to replenish those that are consumed in the periphery. Unfortunately, infection also has deleterious effects injuring hematopoietic stem cells (HSC), inefficient hematopoiesis, and remodeling and destruction of the microenvironment. Despite its central role in immunity, the role of the microenvironment in the response to infection has not been systematically investigated. Here we summarize the key experimental evidence demonstrating a critical role of the bone marrow microenvironment in orchestrating the bone marrow response to infection and discuss areas of future research.